Viralitas Trash Talking di Media Sosial Tiktok sebagai Gaya Baru Personal Digital Branding - Afif Wilanda Anaqhi; Zainal Abidin Achmad; Saifuddin Zuhri; Heidy Arviani (Jurnal Nomosleca, 2023)
Trash-talking Tante Lala on TikTok is a new phenomenon on social media. Its content can become a viral trend, and many TikTok users like it. The viral trash-talking content of Tante Lala shows that the dissemination that occurs involves the participation of TikTok users. This study explores the motivations of followers who make trash-talking viral content, the disseminationâ€™s way of Tante Lala's trash-talking content, and TikTok's role in the media-making process. This study uses the virtual ethnographic method to explain the cultural behavior of trash-talking by TikTok users. The results of this study show the various motivations of Tante Lala's followers in making a viral trend of trash-talking content. Furthermore, the trash-talking content of Tante Lala shapes personal branding as an entertaining TikTok account with a distinctive character. Meanwhile, TikTok is an effective digital tool for personal branding for Tante Lala.Â Â